The Influence of Knowledge Sharing on Employee Performance through the Mediation of Workforce Agility - Setiyawan, Achmad Irvan; Gunawan, Asep; Priyono, Dadang (Al-Qalam Institue, 2025)
This study aims to analyze the effect of knowledge sharing on employee performance with workforce agility as a mediating variable. This industry has experienced rapid growth and intense competition, there by demanding improvements in human resource quality. The research method used is quantitative with a survey approach. The research sample consists of coffee shop employees in Cirebon selected using purposive sampling. Data were collected through questionnaires and analyzed using SPSS 26. The results show that knowledge sharing has a positive effect on both workforce agility and employee performance. Workforce agility is proven to be a significant mediating variable that strengthens the relationship between knowledge sharing and employee performance. These findings emphasize the importance of creating a work culture that supports knowledge sharing and enhances workforce agility, enabling employees to quickly adapt to changes in the work environment. The practical implication of this study is that coffee shop management needs to encourage structured knowledge sharing activities and build employee agility capacity to improve sustainable business competitiveness.